Fig trees at the northern limit of their range: the distributions of cryptic pollinators indicate multiple glacial refugia - CHEN, YAN; COMPTON, STEPHEN G.; LIU, MIN; CHEN, XIAO-YONG (Molecular ecology, 2012)
Climatic oscillations during the last few million years had well‐documented effects on the distributions and genomes of temperate plants and animals, but much less is known of their impacts on tropical and subtropical species. In contrast to Europe and North America, ice‐sheets did not cover most of China during glacial periods, and the effects of glacial cycles were less dramatic. Fig trees are a predominantly tropical group pollinated by host‐specific fig wasps. We employed partial mitochondrial COI (918 bp) and nuclear ITS2 (462 bp) gene sequences to investigate the genetic structure and demographic histories of the wasps that pollinate the subtropical Ficus pumila var. pumila in Southeastern China. Deep genetic divergence in both mitochondrial (7.2–11.6%) and nuclear genes (1.6–2.9%) indicates that three pollinator species are present and that they diverged about 4.72 and 6.00 Myr bp. This predates the Quaternary ice ages, but corresponds with the formation of the Taiwan Strait and uplifting of the Wuyi–Xianxia Mountains. The three pollinators have largely allopatric distribution patterns in China and display different postglacial demographic histories. Wiebesia spp. 1 and 2 occupy, respectively, the northern and southern regions of the mainland host range. Their populations both underwent significant postglacial spatial expansions, but at different times and at different rates. Wiebesia sp. 3 is largely restricted to northern islands and shows less evidence of recent population expansion. Their mainly allopatric distributions and different demographic histories are consistent with host plant postglacial expansion from three distinct refugia and suggest one mechanism whereby fig trees gain multiple pollinators.